Decision-Making in a Context of Uncertainty - Laidoune, Abdelbaki (12th Chaotic Modeling and Simulation International Conference, 2019)
The decision process is considered as the key element for the smooth behavior of systems. For non-complex or linear systems, this process usually follows clear rules or requirements, so that the decision will be easy to make without any difficulty. In the case of complex (non-linear) systems, the decision-making process is repeatedly challenged problems because of the interactions of several factors at the same time and because of the hazards characterizing these factors. This situation will worsen further if the system goes out of its normal operating range to fall into uncertainty. In this paper, we will try to make our contribution, to arrive at simplifying the decision-making process, while playing on human factors (ability, anticipation, risk-taking, etc.). As this process can be improved by the development of intelligent decision support tools.